DIGITAL LABOUR PLATFORMS AND ITS IMPACT ON EMPLOYMENT RELATIONS - Božičić, Darko M (Zbornik radova Pravnog fakulteta u Novom Sadu, 2020)
Information tehnology made significant changes in our everyday life and there is no exeption in employment relations as well. Within, it brought new actor in demand and supply for labour which is represent in digital labour platforms. Although first impresion is that they are intermediate between labour and need for it, actually they have some functions which are characteristic for employers.But, at the end, main (negative) consequence is up to digital worker. In this paper, our main aim is to highlight work through digital platforms and its impact on legal position of digital workers.
Keywords: crowdwork, digital platforms; digital work; freelancers